Comparative study of flexural strength of four acrylic resins before and after thermocycling process - Ghoveizi, Rahab; Tavakolizadeh, Sara; Raftarifarimani, Aida; Barzanji, Agrin; Afshari, Zahra (Journal of Dental School, 2018)
Objectives Acrylic resins are one of the most important denture base materials in dentistry due to their favourable mechanical and physical properties. The purpose of present study is to compare 4 available acrylic flexural strength properties before and after thermocycling. Methods Acrylic resin specimens of Meliodent (Heraeus Kulzer, Hanau, Germany), Vertex (Vertex-dental BV, Zeist, Netherlands), Mead way (Dental Supplies LTD, Surrey, England) and Versacryl (Keystone, Gibbstown, NJ) prepared according to ISO 20745-2 (in dimensions of 25x7x2 mm). Total of 40 blocks obtained: 10 specimens from each type of acrylic resin made one group. Each group divided into two equal subgroups. Flexural strength of specimens in subgroup 1 measured before thermocycling process whereas same measurement carried out for subgroup 2 after thermocycling (5000 cycles) process. Three-point bending test used for the final measurement. Data were analyzed using two-way ANOVA and Bonferroni post-hoc tests with mean difference significant at the 0.05 level (P < 0.05) Results Mead way acrylic resin showed a higher level of flexural strength (105.98± 4.90 MPa) without thermocycling compared to Meliodent and Vertex resins, however, no significant difference was observed between Mead way and Versacryl resin’s same property. Data analysis revealed that thermocycled Meadway resin had highest flexural strength (90.25±S6.30 MPa) in comparison to other resins (Meliodent, Vertex and Versacryl). Flexural strength appeared significant reduction in all resins after polymerization. Conclusion Mead way resin presented the highest flexural strength in both thermocycled and non-thermocycled resin groups. Nonetheless, thermocycling process resulted in notably lower measurements of flexural strength in Versacryl, Vertex, Meliodent and Mead way resins.